Can Doctors Volunteering Online in Health Virtual Community Achieve Work-Family Balance? - Nor, Norzaila Mohamad; Othman, Nafishah; Yusof, Shafiz Affendi Mohd (International Journal of Engineering and Technology, 2018)
Online volunteering is one of the most evident examples of how information communication technology has influenced volunteerism. Volunteering online is prevalent for its flexibility in terms of time and place, allowing individuals to volunteer at any time or any space that they desire. While the technologies may increase flexibility for doctors volunteering online to respond to their work or family, somehow it also allows the online volunteering work to spill over into work or home life, blur the boundaries between work and family domains, hence increases work-family conflict. This study attempt to develop a conceptual framework associated with the potential of achieving work and family balance among doctors volunteering online in health virtual community. The proposed framework is guided by the work-family Border theory to provide a broader understanding of how the embracement of Internet technology for volunteering affects the negotiation of work-family boundaries. The paper described the important concept in online volunteering and work-family balance, and then reviews the border theory that provides the perspectives in which work-family balance embrace other important domain such as online volunteering.